2019
DOI: 10.1111/fme.12373
|View full text |Cite
|
Sign up to set email alerts
|

Socially induced stress and behavioural inhibition in response to angling exposure in rainbow trout

Abstract: It is well known that fish can learn to avoid angling gear after experiencing a catch‐and‐release event, that is, after a private hooking experience. However, the possible importance of social information cues and their influence on an individual's vulnerability to angling remains largely unexplored, that is, social experience of a conspecific capture. The effects of private and social experience of hooking on the stress response of fish and subsequent catch rates were examined. Hatchery‐reared rainbow trout, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…There is increasing understanding that fish learn to avoid being recaptured after initial private hooking and release experiences (e.g. Klefoth, Pieterek, & Arlinghaus, ; Louvén Wallerius et al, ). Also, gear avoidance behaviour is reported for a range of commercial fishing gears (Arlinghaus et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing understanding that fish learn to avoid being recaptured after initial private hooking and release experiences (e.g. Klefoth, Pieterek, & Arlinghaus, ; Louvén Wallerius et al, ). Also, gear avoidance behaviour is reported for a range of commercial fishing gears (Arlinghaus et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In aquaculture Brijs et al [37,38] have published work where the loggers have been used to measure stress in rainbow trout during farming practices such as netting and grouping. While Prystay et al [33] and Wallerius et al [39] have published work where these heart rate loggers have been used to measure stress due to angling. Presuming that the relationship between temperature, heart rate and calibrated metabolic rate exist over extended period of time, long-term recordings (e.g., for over a year or more) on wild fish can help establish bioenergy models associated with seasonal variations in feeding, migration and spawning.…”
Section: Discussionmentioning
confidence: 99%
“…Catch and release has sublethal effects on fish (e.g., inducing hooking-related injuries and physiological stress responses; Pankhurst and Dedual 1994;Meka and McCormick 2005), which can lead to behavioral changes in released fish, such as decreased activity (Schreer et al 2005;Halttunen et al 2010;Klefoth et al 2011) and altered feeding (Stålhammar et al 2012). The experience of being captured and released can also induce hook avoidance learning, which has been documented in as diverse species as Common Carp (Beukema 1970a;Raat 1985;Klefoth et al 2013), Northern Pike (Beukema 1970b;Arlinghaus et al 2017aArlinghaus et al , 2017b, Largemouth Bass (Anderson and Heman 1969;Wegener et al 2018;Louison et al 2019b), and Rainbow Trout Oncorhynchus mykiss (Askey et al 2006;Lovén Wallerius et al 2019;Koeck et al 2020). Hook avoidance learning decreases overall angling vulnerability and can penalize future catch rates (Beukema 1970a(Beukema , 1970bvan Poorten and Post 2005;Klefoth et al 2013;Monk and Arlinghaus 2017).…”
mentioning
confidence: 99%
“…Mechanistically, hooked and released fish learn from private hooking experiences (Beukema 1970a;Raat 1985;Louison et al 2019b;Lovén Wallerius et al 2019). In addition, it has been suggested that fish may also rely on socially transmitted cues that indicate threat, such as behavioral cues or the release of alarm pheromones (also called Schreckstoff) through injury of the epidermis (Pitcher 1993), to avoid future capture by angling (Beukema 1970a;Klefoth et al 2013;Lovén Wallerius et al 2019;Koeck et al 2020) or other fishing gear (Brown and Warburton 1999;Brown and Laland 2002). Compared to the effects of private learning (i.e., direct effects of hooking), it remains largely unexplored to what extent social learning (i.e., the experience of watching conspecifics being caught) can affect individual vulnerability to capture in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation